L’historiographie de la population anglaise - Sabine Reungoat (Revue Française de Civilisation Britannique)
The development of the “New History” caused a surge of interest in the demographic history of England. This paper highlights the main historiographical trends in English population studies, from the foundation of historical demography in the post-war period, to the more recent contributions of historians and anthropologists to a field long dominated by demographers. While we now possess a reliable set of statistics on the structure and evolution of the English population in both the pre-industrial and industrial periods, thanks to the work of the “Cambridge Group for the History of Population and Social Structure”, the interpretation of observed trends is far from straightforward. The controversy on the causes of the population increase in the XVIIIth century, or the debate on the mechanisms of the demographic transition have led historians to review existing interpretative models, and place more emphasis on the role of social and cultural factors in shaping demographic behaviour.